The Use of Canva's AI Features on Visual and Linguistic Creativity in Creating Advertising Texts in Indonesian Language Learning for Junior High School Students - Fanny Claudia Pangemanan; Fince L Sambeka; Santje Iroth (Riset : Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study aims to describe the use of Artificial Intelligence (AI) features in the Canva application to enhance the visual and linguistic creativity of eighth-grade students in creating advertising texts in Indonesian language learning at SMP Negeri III Manado. This research employed a descriptive qualitative approach to deeply describe the learning process, student work, and student responses to the use of AI-based Canva. The subjects consisted of an Indonesian language teacher and eighth-grade students. Data were collected through learning observations, interviews, and documentation, specifically 20 public service advertisements produced by students on social campaign themes such as energy saving and anti-bullying. Data analysis was conducted using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The results indicate that the use of Canva's AI features, such as Magic Write, Text to Image, and Magic Design, positively contributes to the development of students' visual and linguistic creativity. Visual creativity was evident in students' ability to combine colors, illustrations, typography, and layout harmoniously and attractively. Linguistic creativity was reflected in the use of persuasive diction, effective sentences, and the alignment of the advertisement's content with its purpose and theme. It can be concluded that the use of AI-based Canva strongly supports creative, innovative learning of advertising texts, aligning with the Learning Outcomes (CP), Learning Objective Flow (ATP), and Phase D of the Merdeka Curriculum. Keywords: Canva AI Features, Visual Creativity, Linguistic Creativity, Advertising Text, Indonesian Language Learning.